Factor 49t 6 - 4k 8

Question

Asked 3/2/2015 2:56:09 PM

Updated 3/3/2015 12:37:37 AM

4 Answers/Comments

akosijanryl|Points 343|

latefisher|Points 3420|

rodnix|Points 411|

jeifunk|Points 43626|

yeswey|Points 26599|

christolentino090|Points 60|

erikalui|Points 1666|

x = 20/2

x = 10

grazilda_f|Points 83|

Question

Asked 3/2/2015 2:56:09 PM

Updated 3/3/2015 12:37:37 AM

4 Answers/Comments

Rating

3

x^3 + 6x^2 - 4x - 24

= x^2(x + 6) - 4(x + 6)

= (x^2 - 4)(x + 6)

= (x - 2)(x + 2)(x + 6)

= x^2(x + 6) - 4(x + 6)

= (x^2 - 4)(x + 6)

= (x - 2)(x + 2)(x + 6)

Added 3/3/2015 12:24:05 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [3/3/2015 7:59:08 AM]

3

The solution for 2x + y = 3 , x = 2y - 1 is x = 1 , y = 1 .

put x in equation 1

2(2y - 1) + y = 3

4y - 2 + y = 3

5y = 5

y = 5/5

y = 1

2x + 1 = 3

2x = 2

x = 2/2

x = 1

put x in equation 1

2(2y - 1) + y = 3

4y - 2 + y = 3

5y = 5

y = 5/5

y = 1

2x + 1 = 3

2x = 2

x = 2/2

x = 1

Added 3/3/2015 12:27:40 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [3/3/2015 8:00:02 AM]

3

The solution for 3x + 2y - 5 = 0 , x = y + 10 is x = 5, y = -5 .

put equation 2 in equation 1

3(y + 10) + 2y - 5 = 0

3y + 30 + 2y - 5 = 0

5y = - 25

y = -5

x = -5 + 10

x = 5

put equation 2 in equation 1

3(y + 10) + 2y - 5 = 0

3y + 30 + 2y - 5 = 0

5y = - 25

y = -5

x = -5 + 10

x = 5

Added 3/3/2015 12:37:37 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [3/3/2015 8:00:38 AM]

29,298,637

questions answered

There are no comments.